Women's writings : subjectivities and historicism - Thiruchandran, Selvy; Women's Education and Research Centre (Colombo, Sri Lanka) (Colombo : Women's Education & Research Centre, 2001)
Study on Tamil women writings of the colonial period in Sri Lanka.
Keywords: Tamil literature -- Sri Lanka -- 19th century -- History and criticism; Tamil literature -- Sri Lanka -- Women authors -- History and criticism; Women and literature -- Sri Lanka; Women authors, Tamil -- Sri Lanka; Subjectivity in literature; Historicism in literature